Planting seeds of self-defeat: Effects of unrealistic regulations on the Caraga wood industry and forest conservation - Vicente B. Paqueo; Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2016)
Years of rapid and indiscriminate logging of Philippine forests, coupled with little reforestation, have led to more frequent, widespread, and damaging natural disasters, such as floods, landslides, and other environmental damages. With strong political will and noble intentions, President Benigno S. Aquino III issued Executive Order 23 (EO 23) in 2011. This order sought to protect the country's natural forests by imposing a total ban over logging activities and imposing stronger measures against illegal cutting. Unfortunately, EO 23 intensified the rent-seeking behavior among the regulating agencies and has led to damaging unintended economic and social consequences without accomplishing much of its avowed objectives. Moreover, there are other potentially more effective ways of protecting Philippine forests. On this score, would it possible to achieve a win-win strategy where natural forests are effectively protected without paralyzing the wood industry that provides incomes and jobs?
Keywords: 330; Philippines; deforestation; wood industry; Caraga; forest products; log ban; Executive Order 23; natural forest; illegal logging